Multi-omics reveals effects of diet FNDF/starch level on growth performance and rumen development of Hu sheep - Zhao, Haibi; Wang, Jiqing; Hao, Zhiyun; Yin, Pengfei; Wang, Shanglong; Guo, Yanli; Ren, Chunyan (Frontiers in Microbiology, 2025)
To maximize the utilization of nutritional components in diet to enhance the growth performance of Hu sheep, this study investigates the effects of varying forage neutral detergent fiber (FNDF) to starch ratio levels in the diet on the rumen microbial flora, metabolites and expression in the rumen epithelium through sequencing techniques involving microbiomes, metabolomics and transcriptomes. Thirty-six male Hu sheep (2 months old) with similar weight [(10 ± 0.5) kg] were randomly divided into four groups of nine sheep each, and were divided into groups A (FNDF/starch = 0), B (FNDF/starch = 0.23), C (FNDF/starch = 0.56) and D (FNDF/starch = 1.10) with different FNDF/starch of pelleted rations, respectively. The results indicated that average daily gain (ADG) and average daily feed intake (ADFI) of group B, C and D were significantly higher than group A (p < 0.05); the feed conversion ratio (FCR) of group B was significantly higher than other groups (p < 0.05) and the height of rumen papillae in group B and C was significantly higher than in group A (p < 0.05). Species annotation results of microorganisms were found that the presence of 22 phyla, 33 classes, 62 orders, 120 families, 245 genera and 341 species. Among them, Prevotella_7 (20.170%) and Succinivibrionaceae_UCG_001 (12.28%) were the dominant bacteria at the genus; Bacteroidota (36.66%), Firmicutes (33.06%) and Proteobacteria (25.39%) were dominant at the phylum. A total of 3,907 metabolites were annotated by metabolomic analysis of the rumen content samples and the differential metabolites were mainly enriched in amino acid metabolism, cofactor and vitamin metabolism and lipid metabolism. Rumen epithelial transcriptome sequencing analysis identified 825 (A vs. B), 355 (A vs. C), 818 (A vs. D), 204 (B vs. C), 718 (B vs. D) and 199 (C vs. D) differentially expressed genes (DEGs). DEGs were mainly enriched in pathways related to amino acid metabolism, vitamins metabolism and signaling, etc. Notably, during histidine metabolism, thiamine in the rumen decreased with increasing FNDF/starch levels, while the expression level of the TPK1 in the rumen epithelium increased with rising FNDF/starch levels. In conclusion, diet FNDF/starch levels have a significant effect on growth performance and healthy rumen development of Hu sheep.